Broadband magneto-electric dipole antenna using circular quadrants with SIW technique : MAGNETO-ELECTRIC DIPOLE ANTENNA WITH SIW TECHNIQUE (Indian Journal of Engineering and Materials Sciences (IJEMS), 2023)
Ku (12-18 GHz) band is prominently utilized for specific application areas related to satellite communications. In the proposed work, the essential characteristics of Magneto electric dipole antenna have suitably been described. This antenna has fruitfully been designed by printing L shaped probe feed and four circular quadrants embedding shorted metallic vias. The antenna offers a wideband impedance bandwidth of 2.53 GHz (12.40-14.93 GHz), which is around 19.26 % at center frequency. Moreover, it exhibits good gain and radiation characteristics. An extensive simulation and optimization have been performed using CST-MW-2019 (Computer Simulation Technology Microwave Studio). The fabricated antenna has been verified on VNA (vector network analyzer for S11) and anechoic chamber (radiation characteristics).